2017
DOI: 10.1371/journal.pone.0185818
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 transmission networks in high risk fishing communities on the shores of Lake Victoria in Uganda: A phylogenetic and epidemiological approach

Abstract: BackgroundFishing communities around Lake Victoria in sub-Saharan Africa have been characterised as a population at high risk of HIV-infection.MethodsUsing data from a cohort of HIV-positive individuals aged 13–49 years, enrolled from 5 fishing communities on Lake Victoria between 2009–2011, we sought to identify factors contributing to the epidemic and to understand the underlying structure of HIV transmission networks. Clinical and socio-demographic data were combined with HIV-1 phylogenetic analyses. HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 50 publications
4
45
1
Order By: Relevance
“…FCs in Uganda are characterised by their limited health care and other social services [22,45,46,52,53]. Both Nsazi and Kigungu have one government health facility at health centre II/III level which provide reliable FP information.…”
Section: Discussionmentioning
confidence: 99%
“…FCs in Uganda are characterised by their limited health care and other social services [22,45,46,52,53]. Both Nsazi and Kigungu have one government health facility at health centre II/III level which provide reliable FP information.…”
Section: Discussionmentioning
confidence: 99%
“…Blantyre, Zomba, Lilongwe and fishing villages along Lake Malawi may also be important sources and be sustaining micro-epidemics in the surrounding rural communities. Phylogenetic analysis could be used, as in Uganda [11,12] and South Africa [27], to differentiate between localized and imported strains and determine (for specific communities) where transmission is occurring. Such analyses would provide important information regarding where to locate interventions and what type of intervention would be most effective; e.g., pre-exposure prophylaxis or voluntary mass circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…Migrants and travelers in many SSA countries have been found to engage in riskier behaviors when they are away from home and are more likely to be infected with HIV than non-migrants/travelers. Additionally, several phylogenetic studies of HIV in SSA have shown that in certain communities, strains are being "imported" from other geographic locations [11,12]; the introduction of viral strains may be due to visitors infecting residents, or residents becoming infected when they travel.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering performed based on partial pol was mostly sustained by the env sequences (Fig 2-B), except that two pol clusters were identi ed as 4 clusters because of two env clusters divided into two smaller clusters respectively. Thus, 36 robust clusters including 110 individuals (25.2%, 110/436) were identi ed according the clustering consistency analyzed and reference to relevant literature [14,15] . Of the 110 clustered individuals in the 36 clusters, 78.2% (86/110) were in 32 small clusters (including 2-5 nodes) and 21.8% (24/110) were in four large clusters (including >5 nodes) (Fig 1 and Fig 2).…”
Section: Characteristics Of Transmission Clusteringmentioning
confidence: 99%